ANALISIS KINERJA KEUANGAN PERUSAHAAN PENGAKUSISI SEBELUM DAN SESUDAH MERGER AKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Navisah Navisah; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2013)
The purpose of this study was to analyze whether there is a difference in financial performance (measured by the Current Ratio, Debt to Equity Ratio, Debt to Total Assets Ratio, Total Assets Turn Over, Return on Investment and Net Profit Margin) the acquire in 2 years before and 2 years after merger acquisition. Grouping of the population being sampled is done non-probability conducted by the method of â€œpurposive samplingâ€ and acquired 13 companies the sample population of 19 companies. Analysis of the measured data of different test receipts, before going to the normality test analyzed the data, if the data are not normally distributed then analysis used in this study is a Paired Sample t-test, and if the data are not normally distributed then testing using the Wilcoxon Signed Rank Test using a significance level of 0.05. Test results using paired sample t-test showed that financial performance is measured by analysis of the Current Ratio, Total Asset Turn Over, Return on Investment and Net Profit Margin there is no difference, while for financial performance as measured by analysis of Debt to Total Assets Ratio indicates there financial performance difference between the 2 years before and 2 years post-merger acquisition. Then testing using the Wilcoxon Signed Rank Test showed no difference in financial performance as measured by Debt to Equity Ratio analysis in the 2 years before and after the merger acquisitions.